Controllability of switched DAEs: The single switch case. Issue 1 (December 2014) - Ruppert, Markus G.‐M.; Trenn, Stephan
Abstract We study controllability of switched DAEs and formulate a definition of controllability in the behavioral sense. In order to characterize controllability for switched DAEs we first present new characterizations of controllability of non‐switched DAEs based on the Wong‐sequences. Afterwards a first result concerning the single‐switch case is presented. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)